2011
DOI: 10.1186/1556-276x-6-554
|View full text |Cite
|
Sign up to set email alerts
|

Gold-silver alloy nanoshells: a new candidate for nanotherapeutics and diagnostics

Abstract: We have developed novel gold-silver alloy nanoshells as magnetic resonance imaging (MRI) dual T1 (positive) and T2 (negative) contrast agents as an alternative to typical gadolinium (Gd)-based contrast agents. Specifically, we have doped iron oxide nanoparticles with Gd ions and sequestered the ions within the core by coating the nanoparticles with an alloy of gold and silver. Thus, these nanoparticles are very innovative and have the potential to overcome toxicities related to renal clearance of contrast agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
2
21
0
Order By: Relevance
“…To the best of our knowledge, none of the previous studies have yet explored the one step AMP synthesis of metal NPs/hydrogel biocomposites. The idea is interesting as such material system would possess multi‐functionality that can be used for various applications in the biomedical field, such as anti‐microbial, drug delivery, cancer theranostics, biosensing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, none of the previous studies have yet explored the one step AMP synthesis of metal NPs/hydrogel biocomposites. The idea is interesting as such material system would possess multi‐functionality that can be used for various applications in the biomedical field, such as anti‐microbial, drug delivery, cancer theranostics, biosensing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different types of nanoparticles, metal nanoparticles including gold and silver have widespread use across the biomedical sciences [3, 4]. Nanoparticles (NPs) based on noble metals remain promising anticancer agents capable of enhancing existing surgery and chemotherapeutic-based approaches in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Five characteristic peaks (111), (200), (220), (311), and (222) confirmed that the Au-Ag alloy was in the fcc structure [13,30]. The peak corresponding to the {200} plane was more intense than the other planes, suggesting that the {200} plane was the predominant orientation, which demonstrated that the nanoscale Au-Ag alloys are high crystalline [7,31]. …”
Section: Resultsmentioning
confidence: 94%